Nanostructures - Ameen, Sadia; Shaheer Akhtar, M.; Shin, Hyung-Shik (IntechOpen, 2020)
This book highlights the functionality, significance, and applicability of nanostructure materials. The chapters in this book provide the logical and comprehensive information pertaining to the recent advances in the synthesis, characterization, and application of nanostructure materials for energy conversion and sensors. Written by an outstanding group of experts in the field, this book presents the latest advances and developments in nanostructure materials. We hope this book will help in describing the current position of nanostructure materials in the technological sphere as well as encourage scientists and engineers in deeper exploration of nanostructure materials to boost the technological advancement.